Taxonomic and functional structure of understorey bird assemblages on Amazonian seasonally flooded river islands - De Jesus Diniz, Priscilla; Baccaro, Fabrício beggiato; Borges, Sérgio henrique (Biological journal of the Linnean Society, 2023)
The seasonal inundation of the floodplains of the Amazonian rivers is a natural and strong environmental filter for biota. Its effects on the taxonomic and functional attributes of assemblages, however, remain poorly understood. We investigated the taxonomic and trait diversity of understorey bird assemblages on fluvial islands subject to dramatic seasonal flooding in the Amazon. Birds were captured using mist-nets on ten fluvial islands and at 17 sites in unflooded terra firme forests. We captured 1552 individuals of 116 bird species in 4144 net-hours. Average capture rates were similar between the forest types, but species diversity was higher in terra firme forests. The bird assemblages of the islands showed higher species dominance, with only three species accounting for 47% of the individuals captured. Functional space was occupied similarly in both bird assemblages, as indicated by functional dispersion indices (Fdis). In contrast, functional evenness (Feve) was lower in the river island assemblages indicating that the dominant species share similar traits. Functional divergence indices (Fdiv) showed substantial niche differentiation between the bird assemblages of the two forest types. Low inter-annual variability in avian taxonomic and trait diversity was observed in river islands, probably associated with the predictability of the flooding regime.